2015
DOI: 10.1093/nar/gkv467
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation processes of copper complexes in DNA

Abstract: The family of anticancer complexes that include the transition metal copper known as Casiopeínas® shows promising results. Two of these complexes are currently in clinical trials. The interaction of these compounds with DNA has been observed experimentally and several hypotheses regarding the mechanism of action have been developed, and these include the generation of reactive oxygen species, phosphate hydrolysis and/or base-pair intercalation. To advance in the understanding on how these ligands interact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
98
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(105 citation statements)
references
References 77 publications
3
98
2
2
Order By: Relevance
“…So copper complexes are regarded as one of the most promising alternatives to cisplatin as anticancer substances. Copper complexes called Casiopeínas have proved their significant anticancer activity, both in preclinical in vitro and in vivo testing, and two of them have entered Phase I of the clinical trials . Zuo et al have reported two amino acid Schiff‐base copper complexes, which could inhibit the chymotrypsin‐like activity of 20S proteasome, cause accumulation of proteasome target proteins bax and IκB‐α, and induce growth inhibition and apoptosis in MDA‐MB‐231, MCF‐7, and PC‐3 tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…So copper complexes are regarded as one of the most promising alternatives to cisplatin as anticancer substances. Copper complexes called Casiopeínas have proved their significant anticancer activity, both in preclinical in vitro and in vivo testing, and two of them have entered Phase I of the clinical trials . Zuo et al have reported two amino acid Schiff‐base copper complexes, which could inhibit the chymotrypsin‐like activity of 20S proteasome, cause accumulation of proteasome target proteins bax and IκB‐α, and induce growth inhibition and apoptosis in MDA‐MB‐231, MCF‐7, and PC‐3 tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…All geometrical optimizations were carried out at the DFT (B3LYP) [58,59] level of theory with 6-31+G* basis set for C, N, O, S, Cl, Br, H and DZpdf [60] for the copper center using Gaussian 09 program [61]. In order to check the binding modes of the copper nucleases, three DNA sequences were used in the verified docking studies: d(5'-ATATATATATAT-3')2 (assigned as DNA1) which is AT-rich sequence, d(5'-CGCGCGCGCGCG-3')2 (assigned as DNA2) which is GC-rich sequence and d(5'-CGCGAATTCGCG-3')2 (assigned as DNA3) which not only contains AT base pair but also contains CG one and is mostly used in molecular docking studies [62][63][64][65]. Three DNAs adopted in this study are B-DNA , which were built by 3DNA [66].…”
Section: Initial Structuresmentioning
confidence: 99%
“…Even though experimental results have demonstrated the DNAcleavage activity of some copper nucleases, the investigations of nuclease-DNA binding modes and cleavage mechanisms of DNA by copper nucleases at the molecular level remain limited. The theoretical approaches provide a powerful tool to evaluate the metal-based compounds interactions with DNA [26][27][28][29][30][31][32][33][34][35]. To the best of our understanding, in the light of available information, the mechanism of nuclease-DNA binding and its effect on DNA secondary structure have not been comprehensively studied in a systematic manner.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, copper complexes are regarded as some of the most promising metal alternatives to platinum compounds in cancer treatment . Copper complexes called Casiopeínas ® have proved their anticancer activity in both preclinical in vitro and in vivo testing, and two of them have entered Phase I clinical trials . Zuo et al .…”
Section: Introductionmentioning
confidence: 99%